Assessing the Effect of Agricultural Practices on Vegetable Production in Home Gardens in Urban Areas: A Case Study of Mukono Municipality. - Joyce Bikay Bya Nguba (Uganda Christian University, 2025)
In response to rapid urbanization and its related challenges such as land unavailability and food security concerns, urban residents have increasingly turned to home-side gardening as a strategy to strengthen food security and generate supplementary income. This study explored the influence of agricultural practices on vegetable production within urban home gardens in Mukono Municipality, Uganda. The study investigated the impact of socioeconomic factors on vegetable production, categorized the agronomic practices in use, and assessed their effects on household food security. Employing a descriptive research design, data were collected from 100 randomly selected households operating home gardens between January and March 2025. Multiple regression analyses using SPSS were employed to clarify the relationships among the key variables. The study revealed that garden size and the type of vegetables grown were the most significant predictors of productivity (R² = 0.709), with exotic varieties bringing considerably higher yields than indigenous ones even though 62% of respondents showed a preference for indigenous vegetables. The research also highlighted a strong adherence to traditional practices, with 90% of participants using local seeds and manual harvesting techniques, and 63% favoring organic fertilizers. Additionally, five essential agronomic practices—nutrient management (B = 3.842, p = 0.003), planting method (B = 3.318, p = 0.008), pest management (B = 2.752, p = 0.012), watering practices (B = 2.152, p = 0.021), and spacing (B = 1.954, p = 0.036)—were identified as significant influences on production outcomes. The food security analysis demonstrated that home gardens contributed approximately 20-28% of recommended daily vegetable intake, with 83% of households achieving moderate to high food security through gardening. For commercial producers, garden-generated income covered 25-40% of household food expenses, enhancing economic food access. This research highlights the importance of home gardens in urban food systems and provides evidence-based recommendations for agricultural extension services to enhance vegetable production in urban settings.
Undergraduate